Critical assessment of right to safe water and sanitation in a South African informal settlement: a case study of Marikana, Cape Town - Danti, Ntomboxolo (Urban Water Management, 2018)
The Bill of Rights in the Constitution of South Africa mandates the promotion of human dignity, equality, and freedom. To attain these three mentioned aspects, the Bill of Rights stipulates that every person has the right to safe water and sanitation and this is done to improve the welfare of every citizen. South Africa has approximately 13% (7.27 million) of its population staying in informal settlements. Most of these informal settlements were formulated during the land invasion and so on and has since been increasing throughout South Africa. This study sought to assess whether informal dwellers have access to safe water and sanitation, what is the state of the water and sanitation facilities. The assessment was conducted in terms of the Bill of Rights in the Constitution of South Africa and WHO. Marikana informal settlement in Cape Town was used as a case study. Safe water and sanitation to all remain a challenge in South Africa, notwithstanding the commendable efforts since 1994, to provide access to safe water and sanitation as a right to all people. Based on empirical findings and analysis of relevant documents, the study views the water and sanitation in SA informal settlements as unsafe. The sanitation facilities are inadequate thus contributing to existing open defecation. The coverage of the water and sanitation facilities is not enough, therefore, compromising the right to access safe water and sanitation. The findings show evidence of non-operational water supply infrastructure. The uncleanliness of the existing sanitation facilities contributes to health issues like water-borne diseases. The sanitation facilities lack the human right factor, for an example, facilities are not designed to accommodate the elderly and physical disable people. Though South Africa made commendable progress in providing access to water and sanitation nationally, the inequality in the provision of safe water and sanitation exists; there is lack of freedom due to the poor safety of public facilities and overcrowded settlements, and the protection of human dignity is still an issue in informal settlements. In general, while the study identifies the existence of comprehensive national legislative and policy frameworks in support of providing safe water and sanitation in informal settlements, there are various challenges such as availability of land, inadequate housing, policy implementation, infrastructure maintenance and so on, that hinder the right to safe water and sanitation and has a possibility to hinder the fulfillment of South Africa's vision 2030 goal to provide access to piped water and flush toilets by all people.